Web-Based Learning Path with Create Interest, Explore Concepts, Reflect, Discuss, Act, Conclude and Share for Developing Student Responsibility: Alur Pembelajaran Berbasis Web dengan Ciptakan Ketertarikan, Eksplorasi Konsep, Rasakan dan Refleksikan, Diskusi Bersama, Aksi Nyata, serta Simpulkan dan Sebarkan untuk Mengembangkan Tanggung Jawab Peserta Didik - Nuraini, Dewi; Hamdani, Nizar Alam; Nurjamil, Asep; Darmawan, Deni; Rahadian, Dian; Rahayu, Ayu Puji (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Character education in Indonesia requires learning approaches that go beyond content mastery to foster responsibility among students. Specific background: Conventional methods in civic education have proven less engaging and inadequate in cultivating responsible attitudes. Knowledge gap: Limited models exist that integrate technology-driven, interactive approaches with systematic character formation. Aim: This study developed and implemented a web-based CERDAS learning path to foster responsibility in junior high school students, specifically in the context of civic rights and obligations. Results: Using the ADDIE model, six stages of CERDAS (Create Interest, Explore Concepts, Reflect, Discuss, Act, Conclude and Share) were designed and validated. Testing with 30 ninth-grade students demonstrated significant growth in responsibility, reflected in discipline, autonomy, collaboration, and commitment. High validation scores (96% for material, 87% for media) confirmed the product’s feasibility. Novelty: This study introduced a systematic, web-based instructional flow explicitly designed to shape responsibility through interactive civic learning. Implications: The CERDAS model offers a scalable strategy for embedding responsibility into digital civic education, contributing to character-based education in Indonesia and beyond. Highlights Students showed greater responsibility in academic, social, and collaborative tasks. Web-based CERDAS learning path engaged students actively in civic education. Validation confirmed the model is feasible and adaptable for broader use. Keywords: Web-Based Learning, Civic Education, Student Responsibility, Interactive Model, CERDAS Path